Once-daily tasimelteon (VEC-162) for jet lag following transmeridian travel: A multicenter, randomized, double-blind, placebo-controlled trial - Polymeropoulos, Christos M.; Polymeropoulos, Vasilios M.; Czeisler, Emily L.; Fisher, Michaela A.; Smieszek, Sandra P.; Xiao, Changfu; Birznieks, Gunther; Polymeropoulos, Mihael H. (Frontiers in Neurology, 2022)
Jet Lag Disorder is a Circadian Rhythm Sleep-Wake Disorder resulting from a misalignment of the endogenous circadian clock and the sleep and wake pattern required by a change in time zone. Jet lag is most severe following eastward travel. This multicenter, randomized, placebo-controlled clinical trial (JET) assessed the physiological mechanism of jet lag induced by a real-life transmeridian flight and evaluated the efficacy of tasimelteon - a circadian regulator acting as a dual melatonin receptor agonist, in the treatment of Jet Lag Disorder (JLD). Tasimelteon-treated participants slept 76 minutes longer on Night 3 during their second trip (evaluation phase) as compared to their first (observational phase). Over the three travel nights evaluated, transmeridian jet travelers in the tasimelteon group slept 131 minutes more (TST2/3) than those in the placebo group. The JET study demonstrated clinically meaningful improvements in nighttime sleep and daytime alertness in both objective and subjective measures as well as global functioning after a real-world flight. These results suggest that tasimelteon can be an effective therapeutic tool to treat JLD in the context of transmeridian travel.